ESTIMATION OF TOURISM INDICATORS BY ANFIS METHOD IN TURKEY - Hüseyin DİNÇ; Rüştü YAYAR; Mahmut HEKİM (International Journal of Eurasia Social Sciences, 2017)
With the increase in the world's wealth level, the number of people participating in tourism activities has also increased. It becomes a necessity to produce new solutions, new policies and new applications together with new investments. In this context, statistical studies were needed for the solution. It was aimed to eliminate this need in the study.In the study, it was aimed to guide the investor, to determine the direction of the consumer, to offer opportunities to the local people and to help the government to produce policies. Tourism incomes, tourist numbers and occupancy rates for the next three years (2016-2018 period) were estimated by the ANFIS method. Forecasting work was done for Turkey, Mediterranean, Aegean, Marmara and Other Regions. The study has benefited from primary and secondary sources. TURKSTAT, Ministry of Culture and Tourism, Turkish Travel Agencies Association and Turkey Hotel Association were used as primary sources. As secondary data, previous researches, articles, books and reports about the subject have been utilized. Systematic information has been produced to shed light on investors planning units, commercial institutions, commercial organizations and the public in the study. It is now a necessity to extend the tourism to the whole country and to 12 months. Antalya and Istanbul infrastructures and investments were negatively affected from the point reached. In addition, terrorism, wars in neighboring countries, bad relations between countries have resulted in the damage of Turkish tourism. As a result of the study, the recommendations generally focus on the provision of season and zone widths in tourism.